PENERAPAN RESTORATIVE JUSTICE MELALUI DISKRESI KEPOLISIAN DALAM PENYIDIKAN ANAK SEBAGAI PELAKU TINDAK PIDANA DI KEPOLISIAN DAERAH (POLDA) DAERAH ISTIMEWA YOGYAKARTA - Widi Atmoko (Universitas Nasional, 2018)
The purpose of this study is for knowing and examine the legal politics of the implementation of restorative justice in the juvenile justice system in order to realize the effectiveness of handling of child cases at the investigation stage. The type of research used in this study using socio legal research. The results of this study are (1) Politics law Settings interests restorative justice views from system Justice child is with he did action Restorative Justice on conflict laws that occur between parties (victims, perpetrators and community) then urgency approach application Restorative Justice with way diversion (transfer) process from penal law to non penal, becomes dominant for Notice. (2) The factors that become obstacle in applying restorative justice in child crime in Polda DIY are: Concern or the fear of the investigator will be blamed by the leader or the superior of the investigator, no existence the legal umbrella that governs and becomes the basis of legitimacy in making decisions on the investigation process, and not existence procedure or formal procedural mechanism for implement it